P-89 Palliative and end of life care Experiences of people of African and Caribbean dEscent during COVID-19 (PEACE). (19th November 2022) - Dewhurst, Felicity; Tomkow, Louise; Poole, Marie; McLellan, Emma; Kunonga, Patience; Andah, Efioanwan; Todd, Chris; Hanratty, Barbara
Abstract : What we knew: People of African and Caribbean descent are less likely to access palliative and end of life care. It is unclear why they are so poorly served by our services and how COVID-19 has exacerbated this. What we wanted to know: We sought bereaved relatives', health and social care professionals' and community workers' views on experiences of and barriers to palliative and end of life care and suggestions for improvement. Methods: Public recruitment was utilised. Over 150 diverse organisations throughout the UK were contacted. Qualitative semi-structured interviews were conducted with a diverse sample of 26 bereaved relatives and 13 professionals. Findings: There were three key themes: Representation, encompassing discrimination and racism. Personalisation, including culture and the impact of COVID-19. Awareness and Access, including support before and after death and communication and involvement in decision-making. Participants recommend services should: Represent Identify and acknowledge racism and discrimination in palliative care provision. Ensure better representation of African and Caribbean communities within services and in public facing material. Personalise Adapt services to ensure they are culturally and religiously competent: Recognise diversity in cultural and religious needs. Challenge racial and cultural stereotypes. Enable equitable remote engagement. Ensure awareness and education Better integrate services within communities by working with faith/community leaders. Raise awareness of the value of palliative care services in all communities. Provide training/education for professionals to build confidence and competence. Conclusion: Palliative care was perceived as inadequate during the pandemic. Inequities in care provision were exacerbated, to the detriment of people of African and Caribbean descent who were disproportionately and uniquely effected. Palliative care services and local communities could and should learn from each other, to enhance equitable access to appropriate care for all. Significant investment in services and communities may be required.